2008
DOI: 10.1007/s00204-007-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced oxidative myocardial injury: protective role of arjunolic acid

Abstract: Arsenic, one of the most harmful metalloids, is ubiquitous in the environment. The present study has been carried out to investigate the protective role of a triterpenoid saponin, arjunolic acid (AA) against arsenic-induced cardiac oxidative damage. In the study, NaAsO2 was chosen as the source of arsenic. The free radical scavenging activity and the effect of AA on the intracellular antioxidant power were determined from its 2,2-diphenyl-1-picryl hydrazyl radical scavenging ability and ferric reducing/antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(96 citation statements)
references
References 49 publications
11
84
0
1
Order By: Relevance
“…These observations are in accordance with previous studies that revealed histological alterations in heart tissue after arsenic injection (8,32). Pretreatment with montelukast effectively prevented cardiomyocyte necrosis and preserved tissue morphology in As 2 O 3 -induced heart injury in rats, demonstrating the advantageous role of montelukast against As 2 O 3 -induced cardiotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…These observations are in accordance with previous studies that revealed histological alterations in heart tissue after arsenic injection (8,32). Pretreatment with montelukast effectively prevented cardiomyocyte necrosis and preserved tissue morphology in As 2 O 3 -induced heart injury in rats, demonstrating the advantageous role of montelukast against As 2 O 3 -induced cardiotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the depletion in GSH levels was observed after arsenic treatment, which could be explained by an adaptive response to oxidative stress, hence GSH plays a fundamental role in detoxifying arsenic species as well as stimulates the excretion of methylated arsenic compounds, or GSH may be oxidised due to the interaction with the free radicals induced by arsenic (Vahter, 2002). Also, GSH can act as an electron donor for the conversion of arsenic (V) to arsenic (III) (Manna et al, 2008). The decrease in the activity of GPx might result directly from the decreased levels of GSH following As exposure since GPx activity depends on GSH level.…”
Section: Discussionmentioning
confidence: 68%
“…In an experimental study on rabbit aorta as Arch Toxicol (2012) 86:825-830 827 a cardiovascular target, Ma et al (2012) show that inflammatory responses play a critical role in the combined cardiovascular toxicity of As and F. Also, mechanisms involved in combined action of As and aryl hydrocarbon receptor ligands are being investigated (Anwar-Mohamed et al 2012). Indeed, with regard to the different manifestations of toxicity of arsenic (Singh et al 2011), cardiovascular disorders, such as hypertension, atherosclerosis and myocardial injury, are receiving increased interest (Manna et al 2008;Balakumar and Kaur 2009;Chen et al 2012). A mechanism likely to be involved is oxidative stress, connected with activation of eNOS and enhanced the phosphorylation of MLCK (Singh et al 2011).…”
Section: Focal Areas Of Present Researchmentioning
confidence: 99%